FURTHER CHARACTERIZATION OF SLEEP-ACTIVE nNOS NEURONS IN THE MOUSE BRAIN - PASUMARTHI, RAVI K. (2010)
We recently demonstrated that Fos is induced in a subpopulation of cortical neuronal nitric oxide synthase (nNOS)-immunoreactive neurons in three rodent species both during spontaneous sleep (SS) and recovery sleep (RS) after a period of sleep deprivation (SD); the proportion of cortical Fos(+)/nNOS neurons was significantly correlated with non-REM (NREM) sleep delta energy. The present study was undertaken to evaluate the specificity of this state-dependent activation of cortical nNOS cells. The percentage of nNOS neurons that expressed Fos during SD and RS was determined in nine subcortical brain regions and the cortex of the mouse brain; a significantly greater proportion of Fos(+)/nNOS neurons was observed during RS only in the cortex and in none of the nine subcortical regions. The proportion of calretinin-, calbindin- and parvalbumin-immunoreactive cortical interneurons that expressed Fos during SD and RS was also determined. In contrast to cortical nNOS neurons, a higher percentage of Fos(+)/calbindin neurons was found during SD than RS; there were no differences in the proportions of Fos-expressing parvalbumin or calretinin neurons between these conditions. Since the nNOS and calretinin cortical interneuron populations overlap extensively in the mouse brain, triple-labeling with these two phenotypic markers and Fos was undertaken in mice from the RS group to determine which combination of markers could best identify the rare “sleep-active” cortical interneuron population. The proportions of both Fos(+)/nNOS neurons and Fos(+)/nNOS/calretinin neurons far exceeded the proportion of Fos(+)/calretinin neurons during RS, but the proportions of these two cell types were not significantly different during RS. Thus, functional activation of nNOS neurons during sleep appears to be restricted to the cerebral cortex and cortical nNOS cells and nNOS/calretinin cells collectively define a cortical interneuron population that is activated during sleep.